The Influence of Artificial Intelligence (AI) Utilization on Learning Motivation and Creativity of Students - Syahril; Deasy arisanty; Ezer Ayu Salin Nazara; Sulistyo Rini (Gawi: Journal of Action Research, 2026)
The development of AI in education has a significant impact on changing how students learn, think, and create, particularly in enhancing access to information and learning effectiveness. The purpose of this study is to analyze the influence of AI on the learning motivation and creativity of FKIP students at Universitas Lambung Mangkurat. This study employs a quantitative research method with a random sampling technique, involving 125 students enrolled in the Scientific Writing course. Data collection was conducted by distributing a Likert-scale questionnaire with 4 response options to measure the variables of AI, learning motivation, and student creativity. The data analysis technique utilizes the Structural Equation Model (SEM) to determine the influence of the AI variable on student learning motivation and creativity. The results indicate that the utilization of Artificial Intelligence (AI) has a positive and significant influence on student learning motivation. However, the utilization of AI does not have a direct significant influence on student creativity. Conversely, learning motivation is proven to have a positive and significant influence on creativity and acts as a mediating variable. In conclusion, the enhancement of student creativity is more effectively achieved through the increase of learning motivation facilitated by the utilization of AI. Therefore, it is recommended that educators integrate AI with active learning strategies, such as project-based and problem-based learning, and encourage students to use AI as a tool for exploring ideas rather than merely for task completion.